A research on the effect of method study on production volume and assembly line effeciency - (:unkn) unknown (Ege Universitesi, 2014)
Method study which is one of the two basic elements of work study is the most effective methods that are used to produce more effectively with current machines and labor without any need for investment. In this research, the operations in blouse sewing line are analyzed critically and the results of method study which is applied on four operations are investigated. Following that, assembly line balancing is conducted by using Ranked Positional Weight Method considering operation durations which are obtained from method study and current operation times. The aim of this research is to analyze the effects of method study on production volume and assembly line efficiency and to indicate the importance of method studies.
Keywords: Assembly line balancing; Method study; Production volume; Productivity; Ranked positional weight; Sewing; Work measurement